AN INTRODUCTION TO MALAY GRAMMAR - Asmah Omar, 1940-; Rama Subbiah (Dewan Bahasa dan Pustaka, 1995)
This book is divided into two parts. The first part which contains twenty one lessons, deals with the structure of the language. The second part contains fifteen selected passages which may be used for precise, comprehension and translation. This book is based on the research of the authors on the Malay language